Critical State Parameters of Dredged Chennai Marine Clay Treated with Low Cement Content. Issue 7 (2nd October 2016) - Subramaniam, Palanidoss; Sreenadh, Mohanachandra Menon; Banerjee, Subhadeep
Abstract : The present article discusses the stress–strain behavior and critical state parameters of the dredged Chennai marine clay stabilized with low cement content (2.5–10%). A series of one-dimensional consolidation tests and consolidated undrained tri-axial tests are performed on the cement stabilized dredged Chennai marine clay to evaluate the critical state parameters ( λ, κ, M, Г, N ) for varying cement contents and curing days. The results show that the slope of the critical state line M increases with an increase in the cement content. The parameter λ for the treated marine clay increases up to a cement content of 7.5% followed by a reduction. The parameter κ decreases with the addition of cement content. Finally, empirical formulations are proposed to predict the critical state parameters as the functions of the cement's contents and curing days.